A new era on the internet: Facebook.com to face the facebook as a huge social phenomenon - Ekinil, Burçin (İletişim Kuram ve Araştırma Dergisi, 2009)
ABSTRACT: In this study, Facebook is captured as our originating point, to understand this huge phenomenon. We worked on Facebook in the light of the Internet and Web 2.0 studies, where historical and technical part of the study appeared. Then we studied Facebook in terms of its daily usage by the members, where we focused on the well-known features of Facebook. We tried to highlight Facebook’s impacts and its structuring on its users. Within this context, surveys were given to Facebook users through the Internet to discover how Facebook changes people’s lives, at which level its importance lie, and what is special about Facebook. With the help of these surveys, we interpreted its different aspects in various ways such as; ‘psychological’, ‘sociological’, ‘virtual identity versus real identity’, ‘voyeurism’ and ‘Facebook as a public space’, while trying to come up with a deeper understanding and analysis of this phenomena.

ÖZET: Bu çalışmada Facebook, dev bir sosyal fenoman olarak, başlangıç noktası olarak belirlendi. Internet ve Web 2.0 çalışmaları doğrultusunda Facebook araştırmasına başlandı ki bu, tarihsel ve teknik çerçeveyi oluşturdu. Daha sonra, Facebook’un günlük hayattaki kullanım sürecinde, tüm Facebook kullanıcılarının yakından tanıdığı özellikler ele alındı. Facebook’un, kullanıcıları üzerindeki yapılanması ve etkileri araştırıldı. Bu doğrultuda, İnternet üzerinden Facebook kullanıcılarına anketler dağıtıldı ve böylece Facebook’un insanların hayatlarını nasıl değiştirdiği, öneminin hangi seviyede olduğu ve Facebook’un diğer sitelerden ayrımı gibi konular üzerinde duruldu. Anketlerin desteğiyle Facebook; ‘psikolojik’, ‘sosyolojik’, ‘sanal kimliğe karşı gerçek kimlik’, ‘röntgencilik’ ve ‘kamusal bir alan olarak Facebook’ alt başlıklarıyla incelenerek, derinlemesine bir anlayış ve analize gidildi.